Enhancing the Catalytic Performance of Candida antarctica Lipase B by Chemical Modification With Alkylated Betaine Ionic Liquids - Xue, Yu; Zhang, Xiao-Guang; Lu, Ze-Ping; Xu, Chao; Xu, Hua-Jin; Hu, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
various betaine ionic liquids composed of different chain lengths and different anions were designed and synthesized to modify Candida antarctica lipase B (CALB). The results showed that the catalytic activity of all modified lipases improved under different temperature and pH conditions, while also exhibiting enhanced thermostability and tolerance to organic solvents. With an increase in ionic liquid chain length, the modification effect was greater. Overall, CALB modified by [BetaineC16][H2PO4] performed best, with the modified CALB enzyme activity increased 3-fold, thermal stability increased 1.5-fold when stored at 70°C for 30 min, with tolerance increased 2.9-fold in 50% DMSO and 2.3-fold in 30% mercaptoethanol. Fluorescence and circular dichroism (CD) spectroscopic analysis showed that the introduction of an ionic liquid caused changes in the microenvironment surrounding some fluorescent groups and the secondary structure of the CALB enzyme protein. In order to establish the enzyme activity and stability change mechanisms of the modified CALB, the structures of CALB modified with [BetaineC4][Cl] and [BetaineC16][Cl] were constructed, while the reaction mechanisms were studied by molecular dynamics simulations. Results showed that the root mean square deviation (RMSD) and total energy of modified CALB were less than those of native CALB, indicating that modified CALB has a more stable structure. Root mean square fluctuation (RMSF) calculations showed that the rigidity of modified CALB was enhanced. Solvent accessibility area (SASA) calculations exhibited that both the hydrophilicity and hydrophobicity of the modified enzyme-proteins were improved. The increase in radial distribution function (RDF) of water molecules confirmed that the number of water molecules around the active sites also increased. Therefore, modified CALB has enhanced structural stability and higher hydrolytic activity